"Appled audio-visual resources fo the teaching of english as a second language for twelfth grade students at Colegio Secundario Las Lajas 2009" - Castro Polanco, Laure Lynn (UDELAS, 2010)
It is important to state here that the purpose of this investigation is to applied didactic methodology supported by audio visual techniques and that are applicable to the content of the twelfth grade english as a second language program, for which study Colegio Secundario Las Lajas was chosen as the target institutions subject of this research.